How Does Wi-Fi Work? - Eboch, M. M. (North Mankato, Minnesota : Pebble, a Capstone imprint, 2021)
This essential volume explores the invisible world behind wireless computer technology. From our homes and workplaces to public coffee shops, Wi-Fi has changed how we connect to the internet and how we send and receive information. The Wi-Fi story spans from the discovery of radio waves to high-speed wireless connectivity. This book covers it all in a relatable and fun way that kids will enjoy.-
Technology timeline.
Name "Mark Weakland" on page 1 of cover.
Includes bibliographical references (page 47) and index.
Keywords: Wireless communication systems -- Juvenile literature; Technological innovations -- Juvenile literature; Internet -- Juvenile literature